Left ventricular aberrant bands in children with innocent murmurs - Özme, Şencan; Özkutlu, Süheyla; Müftüoğlu, Saadet; Baysal, Kemal; Saraçlar, Muhsin; Tuncalı, Tahsin (The Turkish Journal of Pediatrics, 1987)
One hundred children with innocent murmurs are presented in this study. Two-dimensional echocardiography revealed left ventricular aberrant bands in all of these children. Longitudinal bands were found to be associated with pulmonary systolic ejection murmurs, while horizontal bands with Still's murmur. Strong evidence in this study regarding the relationship between innocent murmurs and left ventricular aberrant bands had not previously been clearly demonstrated.
Keywords: left ventricle; aberrant band; innocent murmur; Still's murmur; childhood